Mediateka Babel. YouTube jako temat, rama formalna i platforma sztuki - Wójtowicz, Ewa (Artium Quaestiones, 2020)
The text focuses on the specific features of the so-called 'cinematic turn' within the scope of visual culture emergent within the YouTube platform, particularly during its first, formative years. This turn takes place on the meta-level of the existing circulation of content enabled by YouTube, often being an autothematic reflection on this tool of cultural production. The vernacular aesthetics, a specific formal framework and a particular modus operandi of YouTube became the subject of artistic statements, sometimes in a form of subversive remix. Therefore I think of YouTube as a realm of art because of its meta-media practice that made the cinematic turn visible. It does not rely on straightforwardly understood production of (moving) images, but postproduction, as understood by Nicolas Bourriaud. Moreover, the cinematic turn taking place within YouTube is different from the one practised by the avant-garde of 20th century, due its being not “seeing” or “writing” (as Dziga Vertov understood montage) but rather “overwriting”, to use language more adequate to the described sphere of digital culture. Artists use YouTube as an open library, working with its resources, applying techniques such as postproduction, remix, re-contextualisation and appropriation. Therefore it becomes a multimedia library, a “Mediateca Babel” of a kind, to recall J. L. Borges' idea. The examples mentioned in the text are of a postproductional nature, such as to-camera-performance and subversive “overwriting” of contents enabled with the circulationism typical for social media. Equally important are the strategies of recognising the cultural framework of YouTube, in the context of 20th-century media art history, as well as the platform’s interface. Also, there is the issue of relations between vernacular creativity and the art system because of “capturing” the amateur-generated content and transferring it to mainstream artworld. These examples let me argue that the cinematic turn is a form of postproduction, which enables the hidden mechanisms behind the circulation of moving images in the overloaded global network. The cinematic turn in the context of YouTube does not mean that cinema and its language are at home within this platform. Also, the meta-artistic way of “making” platform art does not turn YouTube into “art platform” (as understood by Olga Goriunova). Nevertheless, platform art may happen in this context as a result of working with the cinematic turn in its vernacular aspect, which makes it possible to reveal its key features and move them to the meta-level.